2013
DOI: 10.1177/0300985813490754
|View full text |Cite
|
Sign up to set email alerts
|

Canine Melanoma Diagnosis

Abstract: Melanoma diagnosis in dogs can be challenging due to the variety of histological appearances of canine melanocytic neoplasms. Markers of malignancy are needed. Receptor for activated C-kinase 1 (RACK1) was found to characterize melanomas in other mammals. We investigated the value of RACK1 detection in the classification of 19 cutaneous and 5 mucosal melanocytic neoplasms in dogs. These tumors were categorized as melanocytomas or benign and melanomas or malignant after evaluation of their morphology, mitotic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…RACK1 has been associated with several signaling pathways, and serves a vital function in tumorigenesis ( 22 ). RACK1 was reported to be overexpressed in multiple cancers including melanoma ( 23 ), gastric cancer ( 24 ), hepatocellular carcinoma ( 25 ) and pulmonary adenocarcinoma ( 26 ). RACK1 is thought to promote tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…RACK1 has been associated with several signaling pathways, and serves a vital function in tumorigenesis ( 22 ). RACK1 was reported to be overexpressed in multiple cancers including melanoma ( 23 ), gastric cancer ( 24 ), hepatocellular carcinoma ( 25 ) and pulmonary adenocarcinoma ( 26 ). RACK1 is thought to promote tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This study pointed at GNB2L1 , coding for RACK1, as a potentially interesting gene in melanoma characterization. Later, this scaffold protein with multiple functions has been described as a good marker for differentiating melanocytoma from melanoma in dog ( Campagne et al, 2013 ) and horse ( Campagne et al, 2012 ). More recently, Campagne et al (2017) showed that RACK1 could cooperate with NRAS Q61K mutation to accelerate melanoma onset and metastasis formation in transgenic mice.…”
Section: Future Directionsmentioning
confidence: 99%
“…The expression of melanocytic markers in canine species has never been assessed in a dedicated study, despite numerous markers already being used in diagnostic environments, particularly for neoplastic lesions, such as amelanotic melanomas 21–24 …”
Section: Discussionmentioning
confidence: 99%